PEMBERIAN EDUKASI TENTANG PROSES LAKTASI IBU MENYUSUI PADA KADER POSYANDU SEBAGAI UPAYA PENCEGAHAN STUNTING - Yanti, Irma; Suryani, Lilis (LPPM Institut Pendidikan Nusantara Global, 2024)
Breast milk is the perfect and best food because it contains the nutritional elements needed for the optimal growth and development of babies. Breastfeeding is an important component in efforts to prevent stunting in toddlers. The prevalence of stunting in Karawang Regency in 2021 was 20.6%, in 2022 and only decreased to 12.9% in 2023. Several reasons, including a lack of understanding about the lactation or breastfeeding process cause mothers who do not provide exclusive breastfeeding. Posyandu cadres are one of the drivers of improving maternal and child health. Therefore, community service has been carried out in the form of cadre training through providing education about the lactation process and lactation management practices in Cadaskertajaya Village, Telagasari District, Karawang Regency to prevent stunting. The result was an increase in respondents' knowledge after receiving education. So it will be useful for cadres to increase the knowledge of breastfeeding mothers to increase the success of mothers providing exclusive breastfeeding.